Tindak Tutur Perlokusi Representatif dalam Acara “Lapor, Pak!” Trans 7 - Dwi, Tifani Dwi Kurniavid; Novitasari, Lusy; Purnama, Ardian Pitra Satya (STKIP PGRI Ponorogo Press, 2024)
Representative speech acts are actions that use speech to bind the speech partner to the truth being conveyed. This research aims to describe the form and function of representative perlocutionary speech acts in the event